Shifting Actors and Strategy in Indonesia’s Disaster Diplomacy After Tsunami Aceh 2004 - Surwandono Surwandono; Ratih Herningtyas (Jurnal Ilmiah Hubungan Internasional, 2019)
ABSTRACTDiplomacy as a foreign policy instrument of certain states to attain its national interest has traditionally been the authority of the central government regarding to its adequate capability and authority than other actors.  Indonesia has high rank on disaster vulnerability in the world. Disasters always have been more understood as lost factors than social capital factors. The 2004 earthquake and tsunami in Aceh was a monumental history how managing disasters became a source of productive political and economic diplomacy. This paper will explain how the issue of natural disasters drove some new actors especially local government which has disaster prone areas to participate on disaster diplomacy activities and develop new strategy to manage and capitalize natural disaster into positive social capital to solve social problems, economic, political and social culture in disaster prone areas. The result of article show transformation of actor perceptions on disasters will affect disaster governance.Keywords: Indonesian disaster diplomacy, local government, para-diplomacy and International cooperation